2019
DOI: 10.31557/apjcp.2019.20.3.727
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Diagnostic Efficacy in a Developing South-East Asian Country

Abstract: Background:Breast cancer, is increasing in prevalence amongst South East (SE) Asian women, highlighting the need for high quality, early diagnoses. This study investigated radiologists’ detection efficacy in a developing (DC) and developed (DDC) SE Asian country, as compared to Australian radiologists.Methods:Using a test-set of 60 mammographic cases, 20 containing cancer, JAFROC figures of merit (FOM) and ROC area under the curves (AUC) were calculated as well as location sensitivity, sensitivity and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Previous studies showed that the interpretive performance varies considerably among radiologists in different countries 2 4 . According to the literature, approximately 62% of radiologists interpret mammograms as part of their workload, but only 10.5% consider themselves breast imaging specialists 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that the interpretive performance varies considerably among radiologists in different countries 2 4 . According to the literature, approximately 62% of radiologists interpret mammograms as part of their workload, but only 10.5% consider themselves breast imaging specialists 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Patient treatment outcomes rely heavily on accurate interpretation of radiologists for the early detection of abnormal lesions on mammography, which is currently the most popular X-ray imaging method used for both diagnostic and screening purposes of breast cancer. It has been shown that the diagnostic accuracy of radiologists in screening mammograms varied significantly across countries ranging from below 50% in developing countries to over 80% in developed nations 2 4 . Although reasons could partly stem from differences in patient populations, variability has also been documented in the interpretative skills of radiologists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiologists were provided with a test-set of breast mammograms and were required to decide the absence or presence of a lesion, and if present, the location of the lesion. At the end of the test-set, radiologists were given a sensitivity (true positives) score, a specificity (true negative) score, and lesion sensitivity score, as well as receiver operating characteristic area under the curve (ROC AUC) and jackknife free response operating characteristic figure of merit (JAFROC FOM) scores, which summarised their mammographic detection efficacy (for methods see Jackson et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Early detection of breast cancer depends on accurate interpretation of breast images by radiologists and is essential to improve efficacy of treatments and patient prognosis. However, data collected by our group through the Breastscreen REader Assessment Strategy (BREAST), 9 an official training program for radiologists in Australia, showed that Vietnamese radiologists displayed low diagnostic efficacy on mammograms with cancer sensitivity rates below 50% 10 compared with approximately 80% in Australia 11 . Although it is similar with the BREAST's findings in other developing countries in Asia, 12 this discrepancy must be addressed to improve the welfare of women.…”
Section: Introductionmentioning
confidence: 98%